An exploratory study of a career counselling intervention with "at-risk" youth - Todd, Carolyn B., 1968- (1996)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1996. Education Bibliography: leaves [139]-157 There has been a growing concern over the nature of programming for "at-risk" youth. A proliferation of studies (Wells, 1990: Gottfredson. 1981; Kelly. 1989: Cross & Markus. 1994: McDonald & Jessell. 1992: Kaplan. 1995) over the last two decades show the importance of a number of factors which the educator should consider when designing and implementing such programs. The data point to the significance of the following variables: socio-economic status, gender, ability, self-efficacy, self-esteem, perception of goals, locus of control, role models, level of motivation and attitude towards school. -- A number of interventions have been designed to assist "at-risk" students to stay in school and achieve better grades. Although many such interventions are comprehensive and require time and financial commitment, more recently there has been a trend towards short-term treatments. In either case, systematic evaluations of the intervention are often lacking, thus, limiting the further application and refinement of such programs. -- In the present study, the investigator implemented and evaluated the Engage program, which is a national short-term career intervention program aimed at empowering "at-risk" youth with the knowledge and skills necessary to succeed in today's society. Twelve students' (10 males and 2 females), who were considered "at-risk", according to the criteria presented in Chapter 3. were selected for participation in this program. -- Perceptions of participants on the program were measured and compared on a pre- and post-test questionnaire. Statements within the questionnaire were initially intended as subcomponents of constructs that answered specific evaluative questions. However, lack of inter-reliability between these sub-components precluded such statistical comparisons. Instead, statements were examined on a case by case basis for changes following intervention. -- Results indicated that the most significant changes were evident within variables measuring locus of control and self-efficacy. It would appear that the treatment allowed students to examine their own lives and begin to exercise some control over it. Despite the brief duration of the program, findings indicated positive changes in many of the variables associated with students considered "at-risk". In some cases, it is not certain whether the program served to better train individuals or instead act as a "reality check", encouraging individuals to start taking control of their lives and learning. This program could be viewed as a readiness tool for students deemed to be "at-risk" of dropping out of the school system. It ought not, however, replace other long-term interventions designed for this clientele.